Pelatihan dan Pendampingan bagi Pelaku usaha mikro dalam melakukan pembukuan sederhana di desa Botubarani kec. Kabila Bone Kab. Bone Bolango - Pratiwi Husain, Siti; Ali, Nurmillah N.; Suila, Muh. Adrifat; Abarang, Citra Vebryanti; Tumatar, Jihan Fahira (Universitas Gajah Putih, Indonesia, 2023)
Micro, Small and Medium Enterprises (MSMEs) are a very important economic sector in Indonesia's economic development. The MSME sector makes a significant contribution to economic growth, job creation, and economic equity. Therefore, we conducted socialization and simple bookkeeping training for MSMEs so that they can advance the income of the people in Botubarani Village. By conducting outreach to the people of Botubarani Village, so that they can introduce information about the importance of simple bookkeeping in this case is the traders in Botubarani Village. With the topic that we raise is